Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
5
Step-by-step explanation:
We are looking for the exponent on z when this is simplified :[tex]\frac{27x^2z^6}{-3x^2z}[/tex]
In order to get this, you do not need to simplify the whole term. Looking at the numerator, we have z multiplied six times divided by one z, getting us x multiplied 5 times. Therefore the exponent on z is 5
Answer: 5
=========================================================
Explanation:
Focus on the z terms only. Ignore everything else.
Up top in the numerator we have z^6
In the denominator we have z without an exponent, but it's identical to z^1
We want to divide z^6 over z^1.
Use this rule: (a^b)/(a^c) = a^(b-c)
We subtract the exponents to say (z^6)/(z^1) = z^(6-1) = z^5
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.